Effects of Physical Activity on the Course of Bronchial Asthma and the Relationship Between Asthma and Competitive Sports - a Review of the Literature - Korczak, Wiktor; Woźniak, Weronika; Magielski, Jakub; Gaszyńska, Monika; Falkowski, Wojciech; Madejska, Maria Anna; Krysińska, Anna; Drzewiecka, Antonina; Drzewiecki, Artur; Rudzka, Aleksandra (Journal of Education, Health and Sport, 2025)
Introduction: The symptoms of bronchial asthma, triggered in response to physical and chemical factors, including allergic and non-allergic ones, contribute to a progressive decline in physical condition, both through a decrease in the frequency of physical exercise practiced by patients and in the lack of symptom control caused by inadequate treatment or coexisting aggravating factors. Due to the frequent development of bronchial hyperreactivity and the prevalence of asthma in athletes, particularly competitive athletes, it was thought until recently that physical activity, whether work-related or sports-related, was inadvisable in asthma. Aim of the study: The purpose of this paper is to summarize the state of knowledge regarding the effects of competitive sports on the development of asthma, and to provide evidence that moderate physical activity can in turn complement its treatment. Materials and Methods: We conducted a comprehensive search of the PubMed electronic database and Google Scholar to identify relevant studies published between 1989 and 2023. Inclusion criteria encompassed studies focusing on human populations, also including studies conducted in animals. Articles in languages other than English, case reports and editorials were excluded. Conclusion: A review of the literature indicates that prolonged and intense exposure of athletes to cold air, inhaled harmful chemicals, hyperventilation and intense exercise can result in increased inflammation in the airways, increased sputum production, smooth muscle contraction and bronchial obstruction. However, a growing number of recent studies indicate that regular and moderate physical activity, such as aerobic training, can help improve the overall cardiopulmonary capacity of patients with asthma, reduce coexisting risk factors such as obesity, and improve symptoms control, reduce inflammation, slow the decline in spirometric parameters and disease progression, particularly in children.